A pilot study of magnetic seizure therapy for treatment‐resistant obsessive–compulsive disorder. Issue 2 (19th September 2020) - Tang, Victor M.; Blumberger, Daniel M.; Weissman, Cory R.; Dimitrova, Julia; Throop, Alanah; McClintock, Shawn M.; Voineskos, Daphne; Rajji, Tarek K.; Downar, Jonathan; Knyahnytska, Yuliya; Mulsant, Benoit H.; Fitzgerald, Paul B.; et al.
Abstract: Background: There is growing interest in the potential of neuromodulation options in treatment‐resistant obsessive–compulsive disorder (OCD). Magnetic seizure therapy (MST), is a new treatment intervention in which generalized seizures are induced with transcranial magnetic stimulation. We conducted a pilot study to assess the efficacy and cognitive effects of MST in patients with treatment‐resistant OCD. Methods: In an open‐label pilot study, participants with treatment‐resistant OCD and a baseline Yale‐Brown Obsessive–Compulsive Scale (Y‐BOCS) scores of ≥16 were treated with up to 24 acute treatments. The primary clinical outcomes were clinical response (Y‐BOCS score reduction ≥30%) and remission (final Y‐BOCS score ≤8). A neurocognitive battery, the Quick Inventory for Depressive Symptoms–Self Report (QIDS‐SR), the Beck Scale for Suicidal Ideation (SSI), and the Quality of Life Enjoyment and Satisfaction Questionnaire‐Short Form (Q‐LES‐Q‐SF) were also completed as secondary measures. Results: Ten participants with OCD who had not responded to medications or psychotherapy enrolled in the study and seven completed an adequate trial (defined as ≥8 treatments). MST was associated with minimal cognitive effects except for some decrease in autobiographical memory and no serious adverse effects. Only one participant met the predefined criteria for response, and none for remission. The baseline and endpoint Y‐BOCS scores were not statistically different. Conclusion: Overall, MST was not beneficial in a small group of patients with treatment‐resistant OCD. At this time, other studies of MST for OCD are not warranted until different coil placements targeting other brain circuits can be proposed.